2018
DOI: 10.1038/s41598-018-31353-1
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediates the anti-obesity effect of calorie restriction in mice

Abstract: Calorie restriction (CR) extends lifespan and elicits numerous effects beneficial to health and metabolism in various model organisms, but the underlying mechanisms are not completely understood. Gut microbiota has been reported to be associated with the beneficial effects of CR; however, it is unknown whether these effects of CR are causally mediated by gut microbiota. In this study, we employed an antibiotic-induced microbiota-depleted mouse model to investigate the functional role of gut microbiota in CR. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 64 publications
12
116
2
Order By: Relevance
“…This suppression of methionine content is key to metformin-induced longevity in C. elegans. On similar lines, several studies have shown that DR and exercise in different species significantly alter the host microbiome [213][214][215][216]. It might be possible then that in addition to metformin, several other pro-longevity interventions might exert their effect through microbial modulation of host mitochondrial dynamics and metabolism.…”
Section: Inter-species Interactions: Microbiome-mitochondria Communicmentioning
confidence: 93%
“…This suppression of methionine content is key to metformin-induced longevity in C. elegans. On similar lines, several studies have shown that DR and exercise in different species significantly alter the host microbiome [213][214][215][216]. It might be possible then that in addition to metformin, several other pro-longevity interventions might exert their effect through microbial modulation of host mitochondrial dynamics and metabolism.…”
Section: Inter-species Interactions: Microbiome-mitochondria Communicmentioning
confidence: 93%
“…62 Fecal microbiota transplantation (FMT) has been reported to confer the beneficial metabolic effects of diet and exercise on diet-induced obese mice; these effects have been associated with bacterial genera including Helicobacters, in particular Helicobacter typhlonius, thus reflecting the genus vulnerability to diet, exercise, and even FMT. 64 Indeed, calorie restriction has been shown to alter the composition of the gut microbiota with significant increases in probiotic genera and a decrease in harmful bacteria such as Helicobacters. 64 Indeed, calorie restriction has been shown to alter the composition of the gut microbiota with significant increases in probiotic genera and a decrease in harmful bacteria such as Helicobacters.…”
Section: Pathog Ene S Is Of Non -Helicobac Ter Pylori Helicobac Termentioning
confidence: 99%
“…63 Furthermore, the gut microbiota mediates the anti-obesity effect of calorie restriction in mice. 64 64 …”
Section: Pathog Ene S Is Of Non -Helicobac Ter Pylori Helicobac Termentioning
confidence: 99%
See 2 more Smart Citations